Common Fixed Point Theorem in a Multiplicative S-Metric Space With an Application - Kanchanapally, Prasad; Raju, V. Naga (Communications in Mathematics and Applications, 2021)
In this paper, we introduce multiplicative \(S\)-metric space as a generalization of multiplicative \(d\)-metric space and investigate its some topological properties. Further, we establish a common fixed point theorem for a pair of self maps in the framework of multiplicative \(S\)-metric space with an application. This result generalizes some fixed point results in the current literature. Finally, we provide an example in support of the result.
Keywords: Multipicative S-metric; Common fixed point; Multiplicative S-convergent sequence; Multiplicative S-complete metric space; Multiplicative S-continuous